A CCD Photometric Study of the Near-Contact System OT CEP - Niarchos, P. G.; Gazeas, K. D. (Baltic Astronomy, 2004)
The first l VRI CCD photometric observations of the eclipsing binary system OT Cep are presented. The new times of minima, combined with the existing ones, are used to determine a new ephemeris of the system. Our light curves are analyzed with light curve synthesis techniques to derive the first geometric and photometric elements of OT Cep. The possible evolutionary status of the system is also discussed.
Keywords: Stars: binaries: eclipsing; stars: individual: OT Cep